Innovative immune mechanisms and antioxidative therapies of intervertebral disc degeneration - Wei, Bingqian; Zhao, Yingjing; Li, Weihang; Zhang, Shilei; Yan, Ming; Hu, Zebing; Gao, Bo (Frontiers in Bioengineering and Biotechnology, 2022)
Intervertebral disc degeneration (IVD) is the basic pathological process of many degenerative diseases of the spine, which is often clinically manifested as spinal stenosis, vertebral segment instability, lumbar and leg pain, cervical spondylosis, intervertebral disc herniation and other diseases, and the patient's nerve roots and spinal cord are compressed and produce a series of corresponding symptoms. It not only makes patients and their families bear a huge pain and psychological burden, but also consumes a lot of medical resources. IVD is usually thought to be related to aging, trauma, genetic predisposition and other factors, and there is a close relationship between IVD and changes in tissue structure and function. IVD pathological processes, including oxidative stress, inflammatory response, matrix destruction, cell senescence, autophagy, apoptosis, sepsis and proliferation, in which the inflammatory response is considered a key link in IVD and low back pain (LBP). This study will illustrate the indispensable role of the oxidative stress and inflammatory response (especially macrophages and cytokines) in the onset, progression and degeneration of IVD.